PROGRAM BIMBINGAN PRIBADI SOSIAL UNTUK MENGEMBANGKAN KETERAMPILAN SOSIAL PESERTA DIDIK HOMESCHOOLING - Fadhil Hardiansyah (Jurnal Bimbingan Penyuluhan Islam, 2020)
Current education is not only in the form of formal education in schools. In its development, there is a Homeschooling Institution which is a school solution for students who have limited time, or have difficulty socializing with people. No different from formal schools in general, in homeschooling is also felt to require a special service program to develop students' social skills. The program referred to in this case is the Social Personal Guidance Program. In formal schools, this program becomes part of the Guidance and Counseling Program which is carried out by the Guidance and Counseling Teacher. In this study, researchers used a qualitative approach with the Case Study method conducted at the Homeschooling Institute. This research was conducted to see the Social Personal Guidance Program that is run to develop the Social Skills of Homeschooling Students. The results of this study, researchers see the Social Personal Guidance Program is run by Homeschooling institutions with several methods in the form of activities. The social tutoring program that has been run by a Homeschooling institution also looks very helpful to students developing their social skills.